Corrosion Inhibitor for X70 Steel using Banana Leaves Extract - Mohammad, Amirul Imran; Embong, Zaidi; Jafery, Khawarizmi; Rahim, Siti Maisarah; Mohd Basir, Mohamad Sidiq (Enhanced Knowledge in Sciences and Technology, 2025)
Corrosion of X70 steel remains a significant challenge across industries, necessitating the exploration of effective and eco-friendly inhibitors. This study investigates the corrosion inhibition properties of banana leaves water extract (BLWE) for X70 steel immersed in a NaCl solution. Several analysis methods were used including FTIR, SEM-EDX and EIS. FTIR was employed to identify the functional groups present in the BLWE. SEM-EDX was used to characterise the elemental composition and morphological structure of the X70 steel surface. Comparison of morphology structure and elemental composition on the sample surface were performed between the pre-immersion test, using raw X70 steel samples, and the post-immersion test, where samples were immersed into different ratios of NaCl solution with BLWE inhibitor. The corrosion rate of the X70 steel samples was evaluated and compared using EIS. FTIR analysis revealed the presence of several functional groups in the BLWE, including hydroxyl (-OH) stretching and carbonyl (C=O) stretching, which contribute to its potential as a an organic anti-corrosion barrier. SEM-EDX analysis showed that the 70% NaCl solution mixed with 30% BLWE inhibitor was the most effective, as evidenced by a high percentage of iron (82.34%) and a low percentage of oxygen (11.51%) after the immersion test. EIS results, Tafel and Nyquist plots, demonstrated that the 70% NaCl solution mixed with 30% BLWE inhibitor provided the best corrosion protection, as indicated by a shift in the Tafel plot to a greater potential applied (V) and Nyquist plot to higher resistance values. These findings confirm that the 70% NaCl solution mixed with 30% BLWE inhibitor is the optimal choice for protecting X70 steel samples.